Western Palaearctic Chelostoma bees of the subgenus Chelostoma (Megachilidae, Osmiini): biology, taxonomy and key to species - Müller, Andreas; Pisanty, Gideon; Dorchin, Achik (Zootaxa, 2025)
Osmiine bees of the subgenus Chelostoma (Chelostoma) are restricted to the Palaearctic. Including the species newly described in the present publication, the subgenus comprises 21 species, 19 of which occur in the Western Palaearctic. Except for two pollen generalists, all species of C. (Chelostoma), whose pollen host preferences have been studied so far, are strict pollen specialists on actinomorphic flowers of a single plant genus, such as Ornithogalum (Asparagaceae) or Ranunculus (Ranunculaceae), of a single subfamily, such as Dipsacoideae (Caprifoliaceae), or of a single family, such as Asteraceae or Brassicaceae. In this study, Lamiaceae are identified as a new host plant taxon of C. (Chelostoma) used by probably three closely related species that are equipped with very long mouthparts and an elongated head, likely representing adaptations for the exploitation of the long-tubed and zygomorphic flowers of this plant family. The females of C. (Chelostoma) nest in insect burrows in dead wood or in hollow plant stems, the colonization of which is facilitated by their very slender and elongated body. They use mud to construct brood cell partitions and nest plugs, which is often reinforced by embedding tiny pebbles and sand grains in its outer surface. The taxonomic revision of C. (Chelostoma) revealed the existence of eight new species: C. dolichocephalum sp. nov. from southeastern Turkey and northern Iraq, C. kurdistanicum sp. nov. from eastern Turkey, northern Iraq and Iran, C. levantense sp. nov. from the Levant, C.meronense sp. nov. from northern Israel, C. miripalpum sp. nov. from southern central Turkey and northern Iraq, C. negevense sp. nov. from southern Israel, C. ornithogali sp. nov. from Turkey, and C. scabiosae sp. nov. from southeastern Turkey and northwestern Iran. Chelostoma dolosum (Benoist, 1935) syn. nov. is newly synonymized with C. mocsaryi Schletterer, 1899.